Sediment provenances shift driven by sea level and Indian monsoon in the southern Bay of Bengal since the last glacial maximum - Liu, Shengfa; Ye, Wenxing; Zhang, Hui; Cao, Peng; Li, Jingrui; Sun, Xingquan; Li, Xiaoyan; Fang, Xisheng; Khokiattiwong, Somkiat; Kornkanitnan, Narumol; Shi, Xuefa (Frontiers in Marine Science, 2023)
The Tibetan Plateau uplift has induced the formation of the largest sediment source-sink system in the northeast Indian Ocean, which has become an ideal region for investigating land-sea interaction processes. However, many questions regarding sediment transport patterns and their controlling factors at different time scales remain unanswered. Therefore, in the present study, a gravity core named BoB-79, based on the southern Bay of Bengal (BoB) was selected to investigate sediment provenance shift and its corresponding mechanism to sedimentary environment change since the last glacial maximum (LGM). The clay mineral compositions are analyzed and the whole core sediments reveal a feature dominated by illite ( 55%), followed by chlorite ( 24%) and kaolinite ( 17%), and the content of smectite ( 4%) is the lowest. A trigonometric analysis of provenance discrimination of clay minerals showed that the Himalayas, together with the Indian Peninsula, represent the main sources of southern BoB sediments, and the last glacial period might have been controlled by the dominant Himalayan provenance, with an average contribution of approximately 90%. However, as a secondary source, the influence of the Indian Peninsula increased significantly during the Holocene, and its mean contribution was 24%, thus, indicating that it had a crucial effect on the evolution process of BoB. The sediment transportation pattern changed significantly from the LGM to the Holocene: in the last glacial period, the low sea level exposed the shelf area that caused the Ganges River connected with the largest submarine canyon in BoB named Swatch of No Ground (SoNG), and the Himalayan materials could be transported to the BoB directly under a strong turbidity current, thereby forming the deep sea deposition center with a sedimentation rate of 4.5 cm/kyr. Following Holocene, the sea level increased significantly, and the materials from multiple rivers around the BoB were directly imported into the continental shelf area. The intensive Indian summer monsoon dominated the transportation process of the terrestrial materials, thereby forming a deposition center in the shallow water area of the continental shelf northeast Indian Ocean; subsequently, the material flux relative to the input to the deep sea area decreased significantly, and the sedimentation rate in the southern BoB decreased to 1.7 cm/kyr.